A New Epigeous Species of Troglobius (Collembola: Paronellidae: Cyphoderinae) from Brazil and Notes on the Chaetotaxy of the Genus - Cipola, Nikolas Gioia; Morais, José Wellington; Bellini, Bruno Cavalcante (Florida Entomologist, 2016)
Troglobius albertonoi sp. nov. (Collembola: Paronellidae: Cyphoderinae) from the Brazilian Amazon is described and illustrated. The shape of the mucro and unguis resemble those of T. ferroicus Zeppelini, Silva & Palacios-Vargas, recently described from Brazil, but the chaetotaxy is distinct. This is the 4th species of the genus and the 3rd from Brazil. Variation within the genus Troglobius of the dorsal chaetotaxy and the geographic distribution are discussed, and an identification key to the species is provided. Troglobius albertonoi sp. nov. is the only known epigeous species of the genus.
Keywords: Arthropod; Biome; Geographical Distribution; Identification Key; Neotropical Region; New Species; Taxonomy; Amapa; Amazonia; Collembola; Paronellidae